Cultural Perspectives in English Translation: The Story of Crow and Snake From Panchatantra - Afshord, Ahmad Ayar; Amirdabbaghian, Amin (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
The problem is that although the culture and language are blended, the linguistic elements sometimes roughly demonstrate cultural dimensions in translated products. In other words, a cultural translation usually demands an understanding of linguistic i.e. culturally bound terms and expressions as well as extra-linguistic elements including cultural ones. Since literature is a nation’s cultural resource, the issue becomes even more complicated when literary translation is being involved. To our knowledge, there is no original Panchatantra left in India and all we have today are translations in different languages. To this end, the Persian version has always been considered the source text since the book was first translated into Persian in 550 CE. Therefore, the English translation of the story Crow and Snake is selected from Panchatantra as the target text and investigated employing Bassnett and Lefevere’s (1992) Cultural Theory with a focus on interpretive Discourse Analysis (DA) as analytical frameworks. The Persian text is the translation of Monshi, reprinted in 2010 and the English translation was done by Ryder in 1925. The findings reveal that the relationship between language and culture still remains complicated, and yet the lack of cultural understanding among the translators leads to violation and distortion of the intended messages and meanings embedded in source texts. It is quite safe then to say that the lack of cultural knowledge highly influences the translation